2012
DOI: 10.1681/asn.2011040369
|View full text |Cite
|
Sign up to set email alerts
|

eNOS Deficiency Acts through Endothelin to Aggravate sFlt-1–Induced Pre-Eclampsia–Like Phenotype

Abstract: Excess soluble fms-like tyrosine kinase 1 (sFlt-1) of vascular endothelial growth factor receptor 1 secreted from the placenta causes pre-eclampsia-like features by antagonizing vascular endothelial growth factor signaling, which can lead to reduced endothelial nitric oxide synthase (eNOS) activity; the effect of this concomitant decrease in eNOS activity is unknown. We tested whether the decrease in nitric oxide occurring in female mice lacking eNOS aggravates the pre-eclampsia-like phenotype induced by incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 44 publications
9
109
0
1
Order By: Relevance
“…Studies using viral overexpression33, 57, 59, 60, 61 or direct infusion of sFlt‐132, 55, 62, 63 have demonstrated a critical role for this anti‐angiogenic factor for induction of hypertension and renal damage during pregnancy. Previous studies using exogenous VEGF infusion have reported reduced circulating sFlt‐1 levels 36, 64.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using viral overexpression33, 57, 59, 60, 61 or direct infusion of sFlt‐132, 55, 62, 63 have demonstrated a critical role for this anti‐angiogenic factor for induction of hypertension and renal damage during pregnancy. Previous studies using exogenous VEGF infusion have reported reduced circulating sFlt‐1 levels 36, 64.…”
Section: Resultsmentioning
confidence: 99%
“…Unable to meet the metabolic demands of the developing fetus because of this compromised arterial blood supply, the placenta enters a chronically hypoxic/ischemic state,27 which activates pathways that increase the production of inflammatory cytokines,20 reactive oxygen species,28 and angiogenic imbalance factors including the soluble form of the vascular endothelial growth factor (VEGF) receptor Flt‐1 (sFlt‐1),29 all of which lead to systemic endothelial dysfunction that is manifested as hypertension 30. Among these, sFlt‐1 has been implicated as a major driver of the preeclampsia syndrome because of its high levels in the plasma of preeclamptic mothers31 and the fact that exogenously administered sFlt‐1 induces a preeclampsia‐like syndrome in pregnant rodents 32, 33, 34, 35…”
mentioning
confidence: 99%
“…We also do not know whether H 2 S will downregulate endothelin synthesis, which was recently shown to be a key downstream signaling pathway that mediates sFlt1-induced vascular disease. 44 Finally, H 2 S is known for its antioxidative and ischemia/hypoxia protective features. 45 Because massive sFlt1 production is thought to be secondary to hypoxia, we suggest that cytoprotection could be another protective effect of H 2 S in the sFlt1-induced phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…96,97 Several recent studies have shown that preeclampsia is a risk factor for BPD and PVD 98 and that disruption of the VEGF and other vascular signaling pathways, including soluble endoglin associated with preeclampsia, may contribute to impaired angiogenesis in preterm infants born to these mothers. [98][99][100][101] Placental overproduction of soluble VEGF receptor-1 (soluble fms-like tyrosine kinase-1 [sFlt-1]), which inhibits VEGF signaling through trapping free VEGF, 102 causes maternal endothelial dysfunction and plays a central role in the pathogenesis of preeclampsia. 99,103,104 Intraamniotic sFlt-1 administration during late gestation impairs lung VEGF signaling and increases apoptosis of endothelial cells in newborn rats, which is followed by reductions in alveolarization and vascular growth, along with biventricular hypertrophy during infancy.…”
Section: Pvd In Bpdmentioning
confidence: 99%